Fatal pulmonary haemorrhage in co-infection with dengue and leptospirosis - Zyneelia Husain,; Hashim E, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Leptospirosis is an emerging infectious disease with worldwide distribution. Its symptoms may mimic a number of other infections such as dengue, malaria, hepatitis and typhoid fever, particularly in tropical countries where these diseases are endemic. Similarly, dengue is an important infectious disease that poses as a public health emergency due to its rapid epidemic spread across the world. Here, we report a fatal case of dengue fever in a patient who was also serologically positive for leptospirosis. Co-infection of both dengue and leptospirosis can lead to an illness with overlapping symptoms and therefore present a clinical diagnostic dilemma to the treating physician. Hence, a high index of suspicion among clinicians is required, especially in high endemic areas. The optimal usage of antigen-based rapid diagnostic tests is essential to aid the clinicians to make timely and accurate diagnosis as well as to start appropriate treatment regimes.